PENGARUH INTELLECTUAL CAPITAL TERHADAP ECONOMIC VALUE ADDED PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2013 - SHELVIANA, FIKA (Jurnal Akuntansi AKUNESA, 2015)
Abstrak The research purpose to analyze the influence of Intellectual Capital as measured by Value Added Intellectual Coefficient (VAIC) to Economic Value Added on banking companies listed on Indonesian Stock Exchange during 2011-2013. The research approach is quantitative approach. The results of this study indicate that Intellectual Capital influence to Economic Value Added. Based on analyze and discussion, the conclusion of banking companies from 2011 until 2013 had been optimal to allocate third component of Intellectual Capital in the form of allocate human resources and structural so that provide positive contribution in an effort companies to get Economic Value Added. Keywords: Intellectual Capital, Value Added Intellectual Coefficient (VAIC), Financial Performance of Banking Companies, Economic Value Added